Asymptomatic Bacteriuria in Patients with Type 2 Diabetes Mellitus - Georgia Matthiopoulou; Petros Ioannou; Anna Mathioudaki; John A. Papadakis; Vasiliki N. Daraki; Angelos Pappas; Sotiris Souris; Sofia Maraki; Chrysoula Stathopoulou; Diamantis P. Kofteridis (MDPI AG, 2023)
Objectives: Asymptomatic bacteriuria (ASB) is a common finding in patients with diabetes. Moreover, patients with diabetes and ASB have a greater risk for symptomatic urinary tract infections and associated severe complications. The aim of this study was to estimate the prevalence of ASB, as well as to identify independent risk factors and related pathogens associated with ASB in female and male patients with type 2 diabetes mellitus (T2D). Methods: This prospective case-control study was performed at the University hospital, and the Venezeleion General Hospital, Heraklion, Greece between 2012 and 2019. All patients with T2D attending the diabetes and hypertension outpatient clinics at both hospitals were enrolled, and data regarding their medical history and clinical and laboratory profiles were recorded. Asymptomatic patients with positive urine cultures were assigned as cases while those with negative urine cultures were designated as controls. Results: A total of 437 adult patients of which 61% were female and 39% were male patients with a mean age of 70.5 ± 9.6 years, were enrolled. The prevalence of ASB was 20.1%, in total. ASB was noted in 27% of female participants and 9.4% of male participants. Higher glycated hemoglobin (OR = 3.921, 95%CI: 1.521-10.109, p < 0.001) and urinary tract infection within the previous year (OR = 13.254, 95%CI: 2.245-78.241, p < 0.001) were independently positively associated with ASB, while higher levels of vitamin B12 were independently negatively associated with ASB (OR = 0.994 per ng/mL, 95%CI: 0.989-0.999, p < 0.001). Conclusions: Development of ASB was associated with specific factors, some of which may be modifiable. Interestingly, high B12 was found to be negatively associated with ASB.